Medidas De Ciberdecepción Para Sistemas Digitales Interconectados: Un Modelo Basado En Agentes Y Grafos De Ataque Bayesiano (2024)
This study proposes a hybrid model based on Bayesian Attack Graphs (BAGs) and Agent-Based Modeling (ABMs) to analyze worm attacks on interconnected networks with a mesh topology. The model, developed in NetLogo, simulates the spread of malware in a structured network, evaluating the impact of various defense policies, such as using decoy nodes to divert attacks, reducing connections between devices to limit malware spread, and periodically conducting a full inventory of devices on the network. Through a detailed sensitivity analysis, the critical variables influencing cybersecurity measures are identified. The results demonstrate that the implementation of cyber deception techniques significantly reduces the impact of attacks.